Phyco-diversity Assessment of Bahuda River Mouth Areas of East Coast of Odisha, India - S. K. Das2, M. Nayak1, J. Jena1, P.K. Panda1; L. B. Sukla1, S. Bhakta1*, (Recent Research in Science and Technology, 2011)
A total of 31 algal samples were collected from 5 sampling sites of various water bodies of Bahuda river mouth areas of Orissa during a collection trip in the month of January 2010. Altogether 36 algal taxa were reported belonging to Cyanobacteria/Cyanoprokaryota, Chlorophyta, Euglenozoa and Bacillariophyta. The species distribution indicates the dominance of green algae followed diatoms and blue green algae. The occurrence of species with respect to trophic status of these water bodies indicate that ditch is more eutrophicated in comparison to mesotrophic pond and oligotrophic river.